1988
DOI: 10.1108/eb024728
|View full text |Cite
|
Sign up to set email alerts
|

Who Is Your Satisfied Customer?

Abstract: What causes consumer satisfaction or dissatisfaction with a product? Two psychological theories are provided as an explanation of the amount of perceived satisfaction. By categorizing consumers on the basis of their “activation level,” the marketer can affect the amount of resulting satisfaction. Doing this may require adjusting pricing, promotional, and distribution policies to suit the categories of “high sensation seekers” and “low sensation seekers.” Marketers of services, among others, may find this consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 7 publications
2
11
0
Order By: Relevance
“…In summary, the study supports previous OSL research [40,75,86,92]. Different mobile communication styles cannot be based only on the existing technology adoption frameworks.…”
Section: Discussionsupporting
confidence: 67%
“…In summary, the study supports previous OSL research [40,75,86,92]. Different mobile communication styles cannot be based only on the existing technology adoption frameworks.…”
Section: Discussionsupporting
confidence: 67%
“…Wang et al [45] suggested that an understanding of unobservable cognitive and psychological attributes of potential buyers would help online sellers find their target customers more effectively. As described by Hanna and Wagle [27], extreme sensation-seekers may respond favourably to products, activities, or services that provide more novelty, risk, and excitement. Moreover, marketers can use sensation seeking as a promotional variable.…”
Section: Discussionmentioning
confidence: 96%
“…However, studies on sensation seeking and normal behaviour are more limited. For example, sensation seeking is related to leisure [6,41,46,49,50], consumer behavior [27,44], and travel behavior [20,36].…”
Section: Introductionmentioning
confidence: 99%
“…In support, Wahlers, Dunn, and Etzel (1986) found that OSL was positively correlated with the exploratory tendency factor, exploration through shopping. Similarly, Hanna and Wagle (1989) concluded that level of consumer effort and stimulation during shopping was positively associated with level of OSL. Mittelstaedt, Grossbart, Curtis, and Devere (1976) found a positive relationship between OSL and adoption of new retail facilities.…”
Section: Efeects Of Person Variables and Desired Valuementioning
confidence: 98%